2021
DOI: 10.1080/23294515.2021.1941414
|View full text |Cite
|
Sign up to set email alerts
|

Should Feedback of Individual Results be Integrated into the Consent Process in African Genomics? Participants’ Views from an HIV-TB Genomics Research Project in Botswana

Abstract: Background: Whilst informed consent is a key component of considering whether individual genomic research results could or should be fed back to research participants, little is known about the views of African research participants on its role. Methods: We carried out a qualitative study to explore views of adolescents and parents or caregivers regarding informed consent for feedback of individual results from a genomics research project in Botswana. We conducted 24 deliberative focus group discussions with 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Although all participants were aware that only pertinent results would be returned, they mentioned the value that they still placed on the non-pertinent findings and negative results as they perceived it as a result which could provide answers to issues relating to future health, for themselves or their child, or offer a chance to be involved in forthcoming research studies. These findings resonate with results of other African and South-African studies considering the parental preferences and expectations of feedback of findings from genomic research studies ( Matshabane et al, 2020 , Ralefala et al, 2021 , Ralefala et al 2022 ). The authors identified that participants expressed a strong interest in receiving secondary results as they were viewed as valuable because they could empower or emancipate individuals or motivate healthier lifestyle choices.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although all participants were aware that only pertinent results would be returned, they mentioned the value that they still placed on the non-pertinent findings and negative results as they perceived it as a result which could provide answers to issues relating to future health, for themselves or their child, or offer a chance to be involved in forthcoming research studies. These findings resonate with results of other African and South-African studies considering the parental preferences and expectations of feedback of findings from genomic research studies ( Matshabane et al, 2020 , Ralefala et al, 2021 , Ralefala et al 2022 ). The authors identified that participants expressed a strong interest in receiving secondary results as they were viewed as valuable because they could empower or emancipate individuals or motivate healthier lifestyle choices.…”
Section: Discussionsupporting
confidence: 88%
“…These ndings resonate with results of other African and South-African studies considering the parental preferences and expectations of feedback of ndings from genomic research studies(Matshabane et al, 2020, Ralefala et al, 2021, Ralefala et al 2022). The authors identi ed that participants expressed a strong interest in receiving secondary results as they were viewed as valuable because they could empower or emancipate individuals or motivate healthier lifestyle choices.…”
supporting
confidence: 84%
“…A qualitative study conducted among parents and caregivers of children and adolescents involved in an HIV-TB genomic study in Botswana reported that almost all participants wanted to receive their genetic results (Ralefala et al, 2021). However, satisfying the research participants’ demand for genomics and genetics analyses remains a debate among researchers and bioethicist communities on the African continent (Kasule et al, 2022; Kisiangani et al, 2022; Mwaka et al, 2021b; Ochieng et al, 2021b; Ralefala, Kasule et al, 2022). While these studies highlight the relevance and benefits of sharing genomics results with participants, a number of ethical concerns such as the possibility of misinterpreting these results, unnecessary worry to the participants and family members, and discrimination have been raised (Kaphingst et al, 2016; Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%